(untitled) (Archaeologia Adriatica, 2008)
The first manifestations of the imperial cult in Illyricum can be noted as early as in the period of Octavianus Augustus, when the collegium Iuliales was formed, whose Vir was noted at Iader. Augustus was the patron of the colony of Iader, hence the primary task of the collegium was the promotion of the cult of the imperial family. At Scardona a Liburnian regional imperial cult, ad aram Augusti Liburnorum, has been documented. This article discusses whether this was preceded by a provincial Illyrian cult, as was the case in Hispania, where the regional cult among the Asturian and Cantabrians was preceded by the organization of a central provincial cult at Tarraco. The Liburnian imperial cult probably originated during the reign of Tiberius, and was systematically organized by his governors Publius Cornelius Dolabella and Lucius Volusius Saturninus. From this period comes an inscription dedicated to the Caesar Nero, the son of Germanicus, who is raising the civitates Liburniae. The restoration of the imperial cult as a whole, hence including that of Liburnia, began with the Flavian dynasty, when Scardona was granted municipal status.